Association between religious/spiritual coping and quality of life among hemodialysis patients in Ecuador - Patricia Bonilla Sierra; Patricia Bonilla Sierra; José Miguel Pérez-Jiménez; José Miguel Pérez-Jiménez; José Miguel Pérez-Jiménez; Denisse Paulina Espinoza Quezada; Giancarlo Lucchetti; Rocío De-Diego-Cordero; Rocío De-Diego-Cordero (Frontiers in Public Health)
There is evidence concerning the association between religiousness and quality of life in hemodialysis patients However, studies carried out in South America are scarce in the literature, particularly in Ecuador. This study aims to investigate the influence of religious/spiritual coping on the quality of life of Ecuadorian hemodialysis patients. This is a cross-sectional study carried out in a reference public hospital in Ecuador. Hemodialysis patients answered a questionnaire including sociodemographics, medical data, quality of life (“Kidney Disease Quality of Life-KDQOL-36), SF-12 and religious/spiritual coping (Abbreviated Religious/Spiritual Coping Scale-Brief-RCOPE). Unadjusted and adjusted models were carried out to investigate the association between religious/spiritual coping and quality of life. A total of 58 participants were included. Hemodialysis patients presented higher levels of positive than negative religious/spiritual coping. Although religious/spiritual positive coping was associated with level of education, the relationship between religious/spiritual coping and quality of life were not statistically significant. Despite the lack of statistical significance, our findings highlight the widespread use of R/S coping among hemodialysis patients, emphasizing the need to integrate spiritual support into clinical care. This study provides valuable insights into a predominantly Catholic population (98.3%) in Ecuador, contributing to the limited research on R/S coping in Latin America. Given the homogeneous religious profile, future studies should include more diverse populations and longitudinal designs to assess its impact on quality of life. The lack of a significant association may be influenced by the religious homogeneity of the sample, as well as factors such as social support and illness perception, warranting further exploration in future research.